Pengembangan Chatbot Pelayanan Akademik Berbasis Arsitektur Hybrid Laravel dan Flask dengan Pattern Matching Regular Expression - Rahman, Fazlul (Fakultas Komputer - Universitas Universal, 2025)
Academic information services demand high precision and near-instant responsiveness. While chatbot adoption in higher education is growing, existing approaches face a technical dilemma: deep learning-based Natural Language Processing (NLP) models often require significant computational resources and are prone to